The Use of Local Ingredients in Shaping Tourist Experience: The Case of Allium ursinum and Revisit Intention in Rural Destinations of Serbia - Tamara Gajić; Sonja P. Veljović; Marko D. Petrović; Ivana Blešić; Milan M. Radovanović; Slavica Malinović Milićević; Ana Milanović Pešić; Yerlan Issakov; Dariga M. Khamitova (Foods)
This study explores the role of Allium ursinum L. in shaping authentic gastronomic experiences and its influence on tourists’ perceptions and revisit intentions in rural destinations. Allium ursinum was selected due to its cultural symbolism, seasonal availability, and traditional culinary use, particularly in Serbia. The study applies the SOR (Stimulus–Organism–Response) model to investigate how cognitive and affective responses elicited by interactions with this plant shape tourist behavior. A structured questionnaire was administered to 336 tourists who had consumed food containing Allium ursinum in ten rural destinations across the Republic of Serbia. The findings emphasize the importance of cognitive responses, such as authenticity perception, knowledge acquisition, and cultural understanding, which in turn influence affective responses, including enjoyment, emotional involvement, and flow state. While positive emotions enhance attachment to local food and revisit intention, the subjective nature of these assessments calls for caution when generalizing. The study contributes to the literature by identifying sensory and emotional mechanisms that link local food ingredients with tourist loyalty. This is the first study to empirically test the SOR model using a local plant ingredient in a rural tourism context.